2021
DOI: 10.1371/journal.pone.0252881
|View full text |Cite
|
Sign up to set email alerts
|

A mechanistic model of methane emission from animal slurry with a focus on microbial groups

Abstract: Liquid manure (slurry) from livestock releases methane (CH4) that contributes significantly to global warming. Existing models for slurry CH4 production—used for mitigation and inventories—include effects of organic matter loading, temperature, and retention time but cannot predict important effects of management, or adequately capture essential temperature-driven dynamics. Here we present a new model that includes multiple methanogenic groups whose relative abundance shifts in response to changes in temperatu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 81 publications
0
14
0
Order By: Relevance
“…The sensitivity analysis results are shown in the Supporting Information, Figure S3. From previous performance tests, the q max,opt fit was best at 40% of the reference values and therefore the parameter selection for optimization was based on the model sensitivity analysis with q max,opt = 40% of reference values (equivalent to q max,opt of 0.6, 1.44, and 2.24 g COD‑S g COD‑B –1 d –1 for methanogen groups m0, m1, and m2, respectively) and α opt = 0.02 d –1 . Model sensitivity analysis suggested that methanogenesis (mainly controlled by q max,opt ) will be rate-limiting for methane production, and q max,opt , α opt , K Scoef , and C Xi,in were chosen as optimization parameters.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The sensitivity analysis results are shown in the Supporting Information, Figure S3. From previous performance tests, the q max,opt fit was best at 40% of the reference values and therefore the parameter selection for optimization was based on the model sensitivity analysis with q max,opt = 40% of reference values (equivalent to q max,opt of 0.6, 1.44, and 2.24 g COD‑S g COD‑B –1 d –1 for methanogen groups m0, m1, and m2, respectively) and α opt = 0.02 d –1 . Model sensitivity analysis suggested that methanogenesis (mainly controlled by q max,opt ) will be rate-limiting for methane production, and q max,opt , α opt , K Scoef , and C Xi,in were chosen as optimization parameters.…”
Section: Resultsmentioning
confidence: 99%
“…The ABM predicts organic matter transformation to methane and carbon dioxide by simulating (i) initial disintegration, hydrolysis, and fermentation of degradable volatile solids (VSd) to VFA through a single first-order reaction and (ii) methanogenesis using Monod kinetics for describing VFA conversion by active methanogens, resulting in the production of methane and carbon dioxide. The ABM explicitly simulates development of a methanogen community and by default includes five methanogen populations, 1 which are active in different temperature ranges. These default settings were initially chosen based on fitting to methane productivity at varying temperatures as reported by Elsgaard et al 25 Here, the numbers of methanogen groups were reduced to three (m0, m1, and m2) to decrease computation time and complexity during parameter estimation.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
See 3 more Smart Citations